A Comparison of Methodical Approaches to Fingerprinting of the Volatile Fraction from Winter Savory (Satureja montana). (11th January 2012) - Rzepa Rzepa, Józef Józef; Sajewicz Sajewicz, Mieczysław Mieczysław; Baj Baj, Tomasz Tomasz; Gorczyca Gorczyca, Patrycja Patrycja; Włodarek Włodarek, Magdalena Magdalena; Głowniak Głowniak, Kazimierz Kazimierz; Waksmundzka-Hajnos Waksmundzka-Hajnos, Monika Monika; Kowalska Kowalska, Teresa Teresa
Abstract : It was the aim of this study to compare the efficiency of the different essential oil extraction methods upon the two winter savory ( Satureja montana ) samples of different origin. The compared techniques were the headspace gas chromatography with mass spectrometric detection (HS-GC/MS) run at the two different headspace temperatures (i.e., at 80 and 100°C) and the three different steam distillation techniques preceding the GC/MS analysis. HS-GC/MS is considered as the technique of the first choice, and the compared steam distillation techniques are recommended, respectively, by Polish Pharmacopoeia, European Pharmacopoeia, and the Polish Patent. Adequate conclusions were drawn as to the advantage of HS-GC/MS (not having the pharmacopoeial recommendation) over the different steam distillation techniques and the drawbacks of each individual analytical procedure were discussed.